Poverty alleviation in Nigeria: The role of Islamic social finance instruments in the redistribution of wealth - Busari, Saheed Abdullahi (2021)
Nigeria is a West African country with abundant resources and natural resources. A member of the Organization of The Petroleum Exporting Countries (OPEC). According to the World Bank statistics, Nigeria’s poverty rate is alarming as it is ranked next after India. Despite the numerous natural resources in Nigeria, poor economic management and governance are considered the factors responsible for the current standard of living in the country. This paper aims to examine the potential opportunities and challenges in employing the Islamic social instrument (Zakat, Waqf & Sukuk) in wealth distribution to alleviate poverty in Nigeria. This research will use secondary data obtained through a library search to explicate the challenges of redistribution wealth in Nigeria and the role of Islamic social financing in the eradication of poverty. It will adopt a descriptive analysis approach to the roles and potential contributions of the existing Islamic social finance platforms towards sustainable redistribution of wealth in Nigeria. The study proposed to explicate the socio-economic potentials in Nigeria's multi-ethnic, cultural, and religious society. It will show how the public and private institutions can explore the opportunities and address the challenges of redistribution of wealth and eradicating poverty through Islamic social financing (Zakat, Waqf & Sukuk) in Nigeria. This paper focuses on how the redistribution of wealth through Islamic social finance instruments (Zakat, Waqf & Sukuk) can enhance poverty alleviation in Nigeria. This paper is novel in its approach to unveiling data about the potential contributions of the Islamic social finance institutions in Nigeria towards redistribution of wealth and eradicating poverty.